Potential and Prospects of Vegetation Recovery in Degraded Lands in India - a Review - Raizada, A.; Dhyani, S. K.; Sharda, V. N. (Indian Forester, 2004)
Continued degradation of natural forests in India and increased anthropogenic pressures on scarce natural resources are issues of concern. The resilience and potential of degraded forests to recover, under protection, on their own towards more complex communities are described in this review paper. The need to involve ’local’ forest dependant communities in forest protection through suitable mechanisms is also highlighted. The appearance of shade loving and shade tolerant species after twenty years of forest fallow cycle and increased species diversity in North-East India, indicates the need for a long fallow cycle after slash and burn agriculture. In the Shiwaliks community protection of forests in watersheds led to significant improvements in species stocking rate. In the ravines of Central India, continued protection led to the appearance of a large number of annual and perennial grasses, herbs and shrub species besides an assortment of tree species. Vegetation development however showed variations with regard to topographical situations. In landslide affected areas in the Himalayas, a period offive to six years was required for pioneer species to be replaced by perennial species. Soil nutrient build up however took several decades to occur, after which stable plant communities established themselves. In areas affected by mining, interventions in the form of suitable soil and water conservation techniques were a prerequisite for vegetation establishment and development. The appearance of early and late colonizers were observed to be directly related to improvements in edaphic conditions. Forest dependant rural communities are often cited to be the culprits with regard to forest exploitation. This paper, on the other hand cites some examples where rural communities have been able to protect, conserve and regenerate large areas of natural forest on their own initiative and by local institutional mechanisms. Participatory planning and inlegrated watershed development, specially in ecologically fragile zones like the Himalayas are essential for ensuring environmental security.